PENERAPAN PEER ASSESSMENT DAN SELF ASSESSMENT PADA TES FORMATIF HIDROKARBON UNTUK FEEDBACK SISWA SMA KELAS X (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2013)
The purpose of this study entitled "Implementation of Peer and Self Assessment To Hydrocarbons Formative Tests as a Feedback of Grade X Students of Senior High School"  was to give the students a feedback to improve their knowledge and to get an innovative assessment method as well. Method used on this study was descriptive. Implementation of peer and self assessment was done through six stages. They were motivating students (75.44%), training of peer and self assessment (71.05%), implementing of formative tests and giving feedback (59.65%), implementing of peer assessment, self assessment and giving feedback (90.35%),  communicating results (100%), and utilizing the results (78.95%). The subjects of the study were 19 grade X students of senior high school. From the implementation of peer assessment, there were 47.37% of students categorized as excellent, 31.58% of students categorized as good, 15.79% of students categorized as adequate, and 5.26% of students categorized less. While from the implementation of self-assessment, there were 57.89% of students categorized as excellent, 15.79% of students categorized as good, and 26.32% of students categorized as adequate. A total of 63.16% of students were satisfied with the feedback given by using peer and self assessment rubric in hydrocarbons formative test. A total of 63.16% of students felt obtaining benefits as a feedback from peer and self assessment rubric. Motivating and training stages were not quite maximal, so the implementation of peer and self assessment were not quite optimal as well. Penelitian dengan judul “Penerapan Peer Assessment dan Self Assessment Pada Tes Formatif Hidrokarbon Untuk Feedback Siswa SMA Kelas X” ini bertujuan memberikan feedback kepada siswa untuk meningkatkan pengetahuannya serta mendapatkan metode penilaian yang inovatif. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Penerapan peer assessment dan self assessment dilaksanakan melalui enam tahapan. Rincian keterlaksanaan setiap tahapan yaitu tahap pemotivasian siswa (75,44%), tahap pelatihan peer assessment dan self assessment (71,05%), tahap pelaksanaan tes formatif dan pemberian feedback (59,65%), tahap pelaksanaan peer assessment, self assessment dan pemberian feedback (90,35%), tahap keterlaksanaan  pengkomunikasian hasil (100%), serta tahap pemanfaatan hasil  (78,95%). Subjek penelitian penelitian ini adalah siswa SMA kelas X sebanyak 19 orang. Dalam pelaksanaan peer assessment, sebanyak 47,37% siswa berkategori sangat baik, 31,58% siswa berkategori baik, 15,79% siswa berkategori cukup, dan 5,26% siswa berkategori kurang. Dalam pelaksanaan self assessment, sebanyak 57,89% siswa berkategori sangat baik, 15,79%, berkategori baik, dan 26,32% siswa berkategori cukup. Sebanyak 63,16% siswa merasa puas dengan feedback yang diberikan dengan menggunakan rubrik peer assessment dan self assessment pada tes formatif hidrokarbon. Sebanyak 63,16% siswa merasa memperoleh manfaat berupa feedback dari rubrik peer assessment dan self assessment. Tahap pemotivasian dan pelatihan yang kurang maksimal menyebabkan pelaksanaan peer assessment dan self assessment kurang optimal.
Keywords: feedback; hidrokarbon; peer assessment; self assessment; hydrocarbons